2019
DOI: 10.1080/15384047.2019.1647052
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of an anti-CD147 antibody for Esophageal cancer therapy

Abstract: Background: Esophageal cancer is a highly aggressive neoplasm. Targeted therapy has been proven to be a promising way for cancer therapy. Here, we report a novel anti-CD147 antibody for esophageal cancer therapy, which is a chimeric antibody with modified glycoform in Fc region. Methods: ADCC assay was used to explore the antitumor efficacy of Metuzumab against esophageal cancer in vitro. Wound healing assay and Boyden Chamber invasion assay were performed to explore whether Metuzumab could inhibit migration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Zhang et al [63] provided evidence that chimeric antigen receptor T cells induced by doxycycline targeting BSG could be used in the treatment of liver cancer. Another study also found that doxycycline inhibited the proliferation of gallbladder cancer cells by downregulating the expression levels of BSG and induced an early apoptosis response in cancer cells [64]. In addition, Wang et al [65] found that metuzumab could inhibit metastasis of esophageal cancer via blocking the function of BSG.…”
Section: Discussionmentioning
confidence: 95%
“…Zhang et al [63] provided evidence that chimeric antigen receptor T cells induced by doxycycline targeting BSG could be used in the treatment of liver cancer. Another study also found that doxycycline inhibited the proliferation of gallbladder cancer cells by downregulating the expression levels of BSG and induced an early apoptosis response in cancer cells [64]. In addition, Wang et al [65] found that metuzumab could inhibit metastasis of esophageal cancer via blocking the function of BSG.…”
Section: Discussionmentioning
confidence: 95%
“…Zhang et al [63] provided evidence that chimeric antigen receptor T cells induced by doxycycline targeting BSG can be used in the treatment of liver cancer. Another study also found that doxycycline inhibited the proliferation of gallbladder cancer cells by down-regulating the expression levels of BSG and induced an early apoptosis response in cancer cells [64]. In addition, Wang et al [65] found that Metuzumab could inhibit metastasis of esophageal cancer via blocking the function of BSG.…”
Section: Discussionmentioning
confidence: 95%
“…These results, although preliminary and confirmed only in a small number of patients, suggest a possible contribution of CD147/basigin upregulation in BRAFi/MEKi resistance. Interestingly, several inhibitors [ 72 ] or an antibody [ 73 ] targeting CD147/basigin have been suggested as potential therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%